Glutamatergic Control of Microvascular Tone by Distinct GABA Neurons in the Cerebellum - Armelle Rancillac; Jean Rossier; Manon Guille; Xin‐Kang Tong; H Geoffroy; Christian Amatore; Stéphane Arbault; Édith Hamel; Bruno Cauli (2006)
The tight coupling between increased neuronal activity and local cerebral blood flow, known as functional hyperemia, is essential for normal brain function. However, its cellular and molecular mechanisms remain poorly understood. In the cerebellum, functional hyperemia depends almost exclusively on nitric oxide (NO). Here, we investigated the role of different neuronal populations in the control of microvascular tone by in situ amperometric detection of NO and infrared videomicroscopy of microvessel movements in rat cerebellar slices. Bath application of an NO donor induced both NO flux and vasodilation. Surprisingly, endogenous release of NO elicited by glutamate was accompanied by vasoconstriction that was abolished by inhibition of Ca 2+ -phopholipase A2 and impaired by cyclooxygenase and thromboxane synthase inhibition and endothelin A receptor blockade, indicating a role for prostanoids and endothelin 1 in this response. Interestingly, direct stimulation of single endothelin 1-immunopositive Purkinje cells elicited constriction of neighboring microvessels. In contrast to glutamate, NMDA induced both NO flux and vasodilation that were abolished by treatment with a NO synthase inhibitor or with tetrodotoxin. These findings indicate that NO derived from neuronal origin is necessary for vasodilation induced by NMDA and, furthermore, that NO-producing interneurons mediate this vasomotor response. Correspondingly, electrophysiological stimulation of single nitrergic stellate cells by patch clamp was sufficient to release NO and dilate both intraparenchymal and upstream pial microvessels. These findings demonstrate that cerebellar stellate and Purkinje cells dilate and constrict, respectively, neighboring microvessels and highlight distinct roles for different neurons in neurovascular coupling.